Bagaimana Kepemimpinan Digital dan Dukungan Organisasi Mempengaruhi Perilaku Kerja Inovatif: Efek Mediasi Kecerdasan Emosional - Muhammmad Zahid Ash-Shidqie; Fatmah Bagis; Hengky Widhiandono; Nawalin Nazah (ITB AAS INDONESIA Surakarta, 2026)
Abstract Efforts to create innovative employee behaviour increasingly depend on the quality of leadership and the psychological condition of individuals in the modern work environment. This study aims to analyse the role of digital leadership and organizational support in shaping innovative work behaviour, with emotional intelligence mediation variables in the microfinance institution sector. The quantitative approach is used through the distribution of questionnaires to respondents who work in microfinance institutions, with a total of 192 respondents. The analysis was conducted using Structural Equation Modelling (SEM) to test the relationship between variables and identify the role of emotional intelligence. The results show that digital leadership contributes positively to innovative work behaviour and significantly increases the emotional intelligence of employees. Organizational support has been shown to increase emotional intelligence, but has no direct effect on innovative work behaviour. In addition, emotional intelligence has a significant mediating role in the relationship between digital leadership and innovative work behaviour as well as between organizational support and innovative work behaviour. These findings confirm that employee emotional readiness is a key factor in maximizing the benefits of organizational digitization. The study provides theoretical contributions on the psychological mechanisms that drive innovation, while offering practical recommendations for organizations to strengthen digital leadership competencies, job support, and emotional intelligence to drive sustainable innovation.